GAMBARAN POLA MAKAN DAN AKTIVITAS FISIK PENDERITA DIABETES MELLITUS DI RW 01 KELURAHAN JAGIR SURABAYA - Novera Herdiani (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2017)
Diabetes Mellitus (DM) is a group of hitrogen disorder characterized by the increased of blood glucose level or hyperglycemia. The number of Diabetes Mellitus patients in 2000 in Indonesia got the biggest 4 rank with prevalence of 8.4 million inhabitants. Therefore, handling Diabetes Mellitus needs diet and exercise to control the disease. The purpose of this study is to find out the description of eating and physical activity patterns of Diabetes Mellitus sufferers in RW 01, Kelurahan JagirSurabaya. The design of the study used was cross-sectional, the sample was 56 people. The variable in this study was eating and physical activity patterns of Diabetes Mellitus patients. The data were collected through questionnaires, then the statistical data were processed descriptively by using common. The result of the study of Eating pattern of Diabetes Mellitus sufferers, 54% of the patients had lack of the calories needs in a day, based on the fulfillment of the diet schedule 70% did notconduct an eating schedule and based on the consumption of sweet foods 68%. The result of physical activity of the diabetics whose age was <30 years was varied 33.33% with the result of less physical activity and optimal physical activity as 4 people (57.14%). The result which was varied that 50% had high school education with less physical activity. Based on the result, it is concluded that all Diabetes Mellitus sufferers (100%) have not met a good eating pattern, physical activity patterns of Diabetes Mellitus patients (30%) have` less physical activity.